La passerelle ottomane - Iyas Hassan (Revue des Mondes Musulmans et de la Méditerranée)
Based on the bio-epic Sīrat al-Malik al-Ẓāhir Baybarṣ according to the Damascene telling edited by Bohas, Diab, Hassan and Zakharia (2000-2021), this contribution aims to question the Turkish identity presented within this folk text from two interrelated perspectives: language and cultural reference. First, the work is concerned with commenting on a group of Arabic expressions and vocabulary derived from the Turkish language, most of which have disappeared from dialectal Levantine Arabic today. Looking beyond language, the imagination which conceived this epic narrative invokes a set of references related to Turkish identity with which it engages in dialogue, effectively transforming the ottoman references into narrative plot points. In the second instance, the links between the various language registers and their fictional use as employed, reveal an effort to determine whether the Turkish elements in the bio-epic are merely “cultural residues”; or whether the relationship between the words or phrases and cultural references serve some specific purpose in the story.